Invasive ctenophore Mnemiopsis leidyi in Norway. (2015) - Hosia, Aino; Falkenhaug, Tone
Abstract : We present data on the occurrence of the invasive ctenophore Mnemiopsis leidyi in Norway after the initial observations made in 2005. Our data comes from several net sampling investigations conducted along the Norwegian coast in 2008–2014, as well as beach seine bycatch from the south coast (September–October 2005–2014). In 2008–2010, M. leidyi occurred in moderate abundances (≤0.56 lobate ind m −3 ) during autumn, with northernmost observations from Trondheimsfjord. Mnemiopsis leidyi was not observed in 2011–2012 and was scarce in 2013, but in 2014 it was again abundant along the south and west coasts. While temperature and salinity conditions along the Norwegian south coast and its fjords are sufficient for survival and reproduction by M. leidyi, temperature may limit egg production rates. Biological factors including food limitation as well as competition and predation by native gelatinous predators can also constrain populations. Mnemiopsis leidyi populations in Norway are likely to exhibit source–sink dynamics, with advective losses and suboptimal conditions preventing overwintering in large areas along the coast. The presence of M. leidyi in the southern North Sea, coupled with the cyclonic circulation pattern, suggests that outbreaks may nevertheless be expected in years with favourable conditions and/or significant inflow from the southern North Sea. Climate change could enhance reproduction of M. leidyi in Norway and protected inner fjords may offer a suitable habitat for establishment of local populations in the future.